Оцінювання ефективності функціонування регіональних підсистем радіомоніторингу з контролю використання радіочастотного ресурсу - Ковшар, В. О. (ХНУРЕ, 2021)
Дисертація присвячена вирішенню задачі розробки науково-методичного апарату оцінювання ефективності регіональних підсистем радіочастотного моніторингу з єдиною системою показників та критеріїв і програмно-алгоритмічного забезпечення для проведення автоматизованих розрахунків з метою підвищення ефективності робіт, пов'язаних з радіочастотним моніторингом та електромагнітною сумісністю РЕЗ. В роботі обґрунтовуються специфіка і показники оцінювання ефективності різнотипних станцій радіоконтролю по комплексному виконанню основних завдань РЧМ і проводиться аналіз отриманих результатів для розроблення рекомендацій. Розроблені науково-методичний апарат і програмно-алгоритмічне забезпечення реалізовані, впроваджені і використовуються у виробничому процесі на Державному підприємстві «Український державний центр радіочастот», що підтверджено відповідними актами. The dissertation is dedicated to solving the urgent scientific and applied problem of increasing the functioning efficiency of regional subsystems of radio-frequency monitoring (RS RFM) in order to increase efficiency in terms of performing work related to radio-frequency monitoring (RFM) and electromagnetic compatibility of electronic equipment by developing a scientific and methodological apparatus for evaluating effectiveness, a system of indicators and criteria for evaluating them, programmatically-algorithmic support for automated calculations. At the same time, the dissertation substantiates the specificity and indicators of evaluating the performance of different types of radio monitoring stations for the integrated implementation of the basic tasks of radio monitoring to optimize their quantitative and qualitative composition in regional radio frequency monitoring subsystems, and also analyzes the results to develop recommendations aimed at developing and modernizing the current state of regional subsystems and radio frequency monitoring systems in general. Information and analytical studies were carried out on the principles of construction, structure, functions, tasks to be solved, technical equipment and radio monitoring facilities of the national RFMs (SRFM) of Ukraine and other countries, on the basis of which the task of assessing the effectiveness of radio monitoring by subsystems and RFM tools was formulated. For the first time, a scientific and methodological apparatus has been created for assessing the technical and industrial (integral) efficiency of the operation of the RFMS for radio monitoring of the actual use of the radio frequency resource (RFR), including an improved system-methodological approach, a space-time-frequency method for covering radio-electronic devices (RED) with radio-frequency monitoring, and methods calculation with a uniform system of indicators and criteria of effectiveness, procedures for calculating and forecast performance at the three levels of the SRFM hierarchy. To implement the automation procedure, software and algorithmic support has been developed for calculating the integrated technical and production and individual production indicators of the effectiveness of radio-frequency monitoring of radio monitoring stations (RMS), RS RFM and SRFM in general, their stationary and mobile components for a given period of time and forecasting them for future periods. Based on the initial data on the actual characteristics of the RS RFM and RMS determined by the method, the above performance indicators were calculated for all RS RFMs, the analysis of which revealed the strengths and weaknesses of radio-frequency monitoring of each RS RFM in monitoring each group of radio technologies and solving each RFM task. The proposed methodology and software and algorithmic support are implemented in the production process and tested at the State Enterprise “Ukrainian State Center of Radio Frequencies”.
Keywords: радіочастотний моніторинг; радіочастотний ресурс; інформаційно-розрахункова система; станції радіоконтролю; radio frequency monitoring; radio frequency resource; information and calculation system; radio control facilities